Genetic risk factors for pediatric-onset multiple sclerosis. (December 2018) - Gianfrancesco, Milena A; Stridh, Pernilla; Shao, Xiaorong; Rhead, Brooke; Graves, Jennifer S; Chitnis, Tanuja; Waldman, Amy; Lotze, Timothy; Schreiner, Teri; Belman, Anita; Greenberg, Benjamin; Weinstock–Guttman, Bianca; et al.
Background: Strong evidence supports the role of both genetic and environmental factors in pediatric-onset multiple sclerosis (POMS) etiology. Objective: We comprehensively investigated the association between established major histocompatibility complex (MHC) and non-MHC adult multiple sclerosis (MS)-associated variants and susceptibility to POMS. Methods: Cases with onset <18 years ( n  = 569) and controls ( n  = 16, 251) were included from the United States and Sweden. Adjusted logistic regression and meta-analyses were performed for individual risk variants and a weighted genetic risk score (wGRS) for non-MHC variants. Results were compared to adult MS cases ( n  = 7588). Results: HLA–DRB1*15:01 was strongly associated with POMS (odds ratio (OR)meta  = 2.95, p  < 2.0 × 10 −16 ). Furthermore, 28 of 104 non-MHC variants studied (23%) were associated ( p  < 0.05); POMS cases carried, on average, a higher burden of these 28 variants compared to adults (ORavg  = 1.24 vs 1.13, respectively), though the difference was not significant. The wGRS was strongly associated with POMS (ORmeta  = 2.77, 95% confidence interval: 2.33, 3.32, p  < 2.0 × 10 −16 ) and higher, on average, when compared to adult cases. Additional class III risk variants in the MHC region associated with POMS were revealed after accounting for HLA–DRB1*15:01 and HLA–A*02 . Conclusion: Pediatric and adult MS share many genetic variants suggesting similar biological processes are present. MHC variants beyond HLA–DRB1*15:01 and HLA–A*02 are also associated with POMS.